2016
DOI: 10.1016/j.tmp.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for tourism development in Iran: Perspectives of Iranian tourism suppliers

Abstract: Iranian tourism industry -despite enormous potentials -has faced a number of challenges including wide ranging nuclear related sanctions, negative imagery in the west and lack of effective management of resources. The aim of this paper is to focus on the perspectives of Iranian tourism suppliers who have a crucial role in the development and success of the tourism industry in the country. The findings of this paper are based on interviews conducted in Iran with representatives of Iranian tourism suppliers from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 4 publications
0
23
0
1
Order By: Relevance
“…More participation and investment of the private sector can be a successful remedy in this case (40). Although the image of Iran is not acceptable enough to convince tourists to visit, researchers suggested that this issue could be solved through local strategies and for the neighbor countries (7). Due to the image of the country in western mass media, it would be more realistic to focus the marketing for the border countries and offer the promotional remedies at a macro level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More participation and investment of the private sector can be a successful remedy in this case (40). Although the image of Iran is not acceptable enough to convince tourists to visit, researchers suggested that this issue could be solved through local strategies and for the neighbor countries (7). Due to the image of the country in western mass media, it would be more realistic to focus the marketing for the border countries and offer the promotional remedies at a macro level.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 comprises the amount of capital investment in tourism by three countries in the region, which represents the investment by Iran as, relatively insignificant. There are two major challenges, which also affect the medical tourism sector: ‘Iran’s negative image in the West, and lack of resources to tackle this negative discourse’ (7).…”
Section: Introductionmentioning
confidence: 99%
“…Iran is not yet an ecotourism destination for international visitors and the market is dominated by domestic travelers (Tavassoli, 2002). More importantly, Iran's tourism industry has been suffering from a range of issues over the past three decades, including the over-reliance on oil revenues, negative imagery, international sanctions, political instability and conflicts in the Middle East region, and poor management (Khodadadi, 2016). The recent nuclear agreementreached in Vienna on 14 July 2015and the subsequent softening of relations with the west has opened the doors to a brighter future for the country (Khodadadi, 2016).…”
Section: Ecotourism Tourism Potential In Iranmentioning
confidence: 99%
“…More importantly, Iran's tourism industry has been suffering from a range of issues over the past three decades, including the over-reliance on oil revenues, negative imagery, international sanctions, political instability and conflicts in the Middle East region, and poor management (Khodadadi, 2016). The recent nuclear agreementreached in Vienna on 14 July 2015and the subsequent softening of relations with the west has opened the doors to a brighter future for the country (Khodadadi, 2016). For instance, the director of Iran's Cultural Heritage, Handicrafts and Tourism Organisation claims 6 that 'Iran plans to annually attract 20 million tourists by 2025 which could generate $30 billion of revenues' (Press TV, 2015).…”
Section: Ecotourism Tourism Potential In Iranmentioning
confidence: 99%
“…Then, 38 Strategic Projects are proposed for Implementation from 2013 to 2020. The estimated cost and priority of each project and programs are determined by the planners [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%